2015
DOI: 10.1167/iovs.14-15905
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Caregivers of Children With Congenital Glaucoma: Development and Validation of a Novel Questionnaire (CarCGQoL)

Abstract: We have developed a psychometrically robust 20-item caregiver derived questionnaire, the CarCGQoL, that is a valid and reliable measure of QoL of caregivers of children with PCG. Given its brevity, it is quick and easy to administer in the clinic, and has potential for use as an outcome measure in clinical trials of treatment of PCG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 36 publications
1
49
1
1
Order By: Relevance
“…5,6 However, when assessing the success of childhood glaucoma treatment, the impact caused by the disease on the quality of life of patients and caregivers should also be assessed because the repercussion of the disease on the quality of life of the latter could come to bear on the quality of the care provided to the patient. 7 In the present study, parents reported worse quality of life than children, according to results for the GQL-15 survey of 32.30 ± 11.56 for children vs. 37.52 ± 14.59 for caregivers (p = 0.001). The parameter that was most closely related to quality of life and visual function was visual field MD for the best eye, with a statistically significant correlation between the result of GQL-15 and visual field MD (children: R = 0.63; p < 0.01 and caregivers: R = 0.81; p < 0.001).…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…5,6 However, when assessing the success of childhood glaucoma treatment, the impact caused by the disease on the quality of life of patients and caregivers should also be assessed because the repercussion of the disease on the quality of life of the latter could come to bear on the quality of the care provided to the patient. 7 In the present study, parents reported worse quality of life than children, according to results for the GQL-15 survey of 32.30 ± 11.56 for children vs. 37.52 ± 14.59 for caregivers (p = 0.001). The parameter that was most closely related to quality of life and visual function was visual field MD for the best eye, with a statistically significant correlation between the result of GQL-15 and visual field MD (children: R = 0.63; p < 0.01 and caregivers: R = 0.81; p < 0.001).…”
Section: Discussionsupporting
confidence: 46%
“…This could impact their education, particularly in the first few months after diagnostic and surgery. 1,7 In some occasions, childhood glaucoma is associated to a systemic disease that will require treatment, thus increasing the need for checkups. 8 At present, in order to assess the impact of chronic diseases such as pediatric asthma 9 or oncological diseases, 10 the caregivers are asked to fill in quality of life questionnaire and the financial impact that said diseases can have on family resources as well as the physical stress that could influence the care given to cover the medical as well as physical and social needs of the children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the measures available for adults with visual impairment (e.g., 37,45,49,67,68,99,120 ), there has been a paucity of effort in the development and application of such measures for children; however, several instruments have recently been developed to target this specific population and are now available for use. 10,23,31,41,42,60,101,103 If future studies would incorporate measures for functional status and/or quality of life as secondary outcome measures, in addition to their primary outcome measures, it would facilitate comparison between studies using meta-analysis.…”
Section: Recommendations For Practice and Future Researchmentioning
confidence: 99%
“…Indeed, existing studies are largely restricted to caregiver burden and QoL in physical illnesses, such as Alzheimer’s disease and leukemia [2934], with little focus on psychiatric illnesses, particularly OCD. Studies in psychiatric conditions have largely focused on schizophrenia [3540].…”
Section: Introductionmentioning
confidence: 99%